2010
DOI: 10.4995/wrs.2007.601
|View full text |Cite
|
Sign up to set email alerts
|

The protective efficacy of vitamins (C and E), selenium and silymarin supplements against alcohol toxicity

Abstract: ABSTRACT:This study aimed at investigating the efficacy of vitamins (C and E), selenium and silymarin (an antioxidant complex from Silybum marianum) supplementation in reducing toxic effects of ethanol on liver weight and some blood parameters. Sixty male rabbits, individually housed in steel cages, were randomly divided into three groups. The first was a control group, the second received balanced diet and daily 20% (v/ v) ethyl alcohol in their drinking water, the third received the same diet and 20% (v/v) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…This is in agreement with the studies of Upansai et al 35 which showed that combined administration of AT and AA inhibits lipid peroxidation induced by lead which may be due to its antioxidant property. This observation was further supported by findings of Shalan et al 7 who proved the protective efficacy of AT, AA, and selenium against ethanol-induced toxicity. Free radical-scavenging enzymes such as SOD and catalase are known to be the first-line cellular defense against oxidative damage and earlier reports have shown that they get reduced after ethanol abuse.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is in agreement with the studies of Upansai et al 35 which showed that combined administration of AT and AA inhibits lipid peroxidation induced by lead which may be due to its antioxidant property. This observation was further supported by findings of Shalan et al 7 who proved the protective efficacy of AT, AA, and selenium against ethanol-induced toxicity. Free radical-scavenging enzymes such as SOD and catalase are known to be the first-line cellular defense against oxidative damage and earlier reports have shown that they get reduced after ethanol abuse.…”
Section: Discussionsupporting
confidence: 73%
“…6 AA, a hydrophilic antioxidant, acts as a free radical scavenger and reduces the capability of ethanol to interact with essential molecules. 7 AA protects lipid peroxidation in hydrophobic compartments either by scavenging lipid peroxides or by reducing tocopherol radicals to tocopherols. 8 Numerous studies have been conducted to elucidate the antioxidant potential of AT 9,10 and AA.…”
Section: Introductionmentioning
confidence: 99%
“…Adimoelja and Adaikan (1997) observed no significant differences in Hb levels, in the liver and kidney biomarker enzymes (ALT, AST, Gamma glutamyl transpeptidase, urea and creatinine) before and after TT treatment. In the same direction, Shalan et al (2007) suggested the hepatoprotective effects of vitamins (C, E), Se and silymarin supplements against alcohol intoxication, these antioxidant supplementations significantly reduced the effect of alcohol intake on serum ALT, AST, ALP and LDH activities. Moreover, Zhao et al (2013) confirmed the Se plus vit E hepatoprotective effect against arsenic-induced liver injury.…”
Section: Discussionmentioning
confidence: 97%
“…Combined treatment with ranitidine and vitamin E protected rat liver from rifampicin induced liver injury (Sapakal et al, 2011). Treatment of male rabbits with vitamin C (1 mg 100 g −1 body weight) and vitamin E (1 mg/100 g body weight) for 2, 4, 6 and 8 weeks ameliorated ethanol induced hepatomegaly, apoptic DNA fragmentation in hepatocytes, normalized alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and LDH activities (Shalan et al, 2007). In a histological examination of the protective effect of vitamin E and vitamin C in cisplatin induced hepatotoxicity, coadministeration of vitamin E (5 mg kg −1 ) and vitamin C (8 mg kg −1 ) to rats for 3months reduced cisplatin induced hepatotoxicity (Tarladacalisir et al, 2005).…”
Section: Science Publicationsmentioning
confidence: 96%